Lymphoscintigraphic evaluation of primary congenital lymphedema - Caner, Biray; Günaydın, Erbengi; Yalaz, Kalbiye; Varoğlu, Erhan; Naldöken, Seniha; Bernay, İrem; Bekdik, Coşkun (The Turkish Journal of Pediatrics, 1990)
A four-year-old girl with primary nonfamilial congenital lymphedema was evaluated by lymphoscintigraphy using 99mTc-Dextran. It was demonstrated that there was no accumulation of radioactivity in the left inguinal and femoral lymph nodes and faint accumulation in the contralateral lymph node. It was concluded that lymphoscintigraphy is a safe, reliable, noninvasive technique which is helpful in the evaluation of a patient with lymphedema, especially small children in whom conventional contrast lymphangiography offers some challenges.
Keywords: primary lymphedema; lymphoscintigraphy; 99mTc-Dextran